Heritage Conservation, UNESCO and Intangible Cultural Heritage in Eastern Canada - MacKinnon, Richard (Ethnologies, 2014)
Since Canada has signed the UNESCO Convention concerning the Protection of the World Cultural and Natural Heritage of 1972, it has had some eighteen cultural and natural sites selected for the World Heritage List that represent internationally significant nature reserves and natural wonders, significant Canadian architectural history, important sites representing Canadian aboriginal culture and geological treasures of world-wide importance. These internationally significant sites have put Canada on the world stage in both the heritage conservation field and in the national and international tourism sector. What Canada has decided to inscribe on this list has had a major impact at the local, regional, national and international arenas. The author of this paper reflects on some of the ancillary guiding charters and conventions since the World Heritage Convention was implemented that have led to where we are today in the field of heritage conservation in Canada. He goes on to predict some areas where heritage conservation will be going in Canada in the near future. He argues that Canada could likewise have its rich intangible culture play a similarly significant role if the Canadian government signed the UNESCO Convention for the Safeguarding of Intangible Cultural Heritage of 2003. Last, he discusses some of the recent developments in eastern Canada in intangible cultural heritage, conservation and the sustaining of traditions.